Happy St. Patrick's day, Hello Kitty (New York : Abrams Books for Young Readers, 2015)
"It's St. Patrick's day, and Hello Kitty is getting ready for the big parade. She puts on her green dress and meets her friends at the parade. Look at all the floats! Listen to all the music! Just as the friends begin their Irish jig, it starts to rain. Oh no! Will it ruin the parade?"--Cover.
Keywords: Children's stories